Characterization of LiBH4–MgH2 Reactive Hydride Composite System with Scattering and Imaging Methods Using Neutron and Synchrotron Radiation. Issue 11 (21st August 2021) - Karimi, Fahim; Börries, Stefan; Pranzas, P. Klaus; Metz, Oliver; Hoell, Armin; Gizer, Gökhan; Puszkiel, Julián A.; Riglos, Maria V. C.; Pistidda, Claudio; Dornheim, Martin; Klassen, Thomas; Schreyer, Andreas
Abstract : Reversible solid‐state hydrogen storage in metal hydrides is a key technology for pollution‐free energy conversion systems. Herein, the LiBH2 –MgH2 composite system with and without ScCl3 additive is investigated using synchrotron‐ and neutron‐radiation‐based probing methods that can be applied to characterize such lightweight metal–hydrogen systems from nanoscopic levels up to macroscopic scale. Combining the results of neutron‐ and photon‐based methods allows a complementary insight into reaction paths and mechanisms, complex interactions between the hydride matrix and additive, hydrogen distribution, material transport, structural changes, and phase separation in the hydride matrix. The gained knowledge is of great importance for development and optimization of such novel metal‐hydride‐based hydrogen storage systems with respect to future applications. Abstract : The composite system LiBH4 –MgH2 with an addition of ScCl3 is investigated, which can reversibly store roughly 10 wt% hydrogen. Synchrotron and neutron methods are applied to probe the structural characteristics of this system from the lab scale up to a real tank system. The results reveal a strong correlation between structural and reversibility properties in this system.